Particulate Matter Detachment from a Magnetizable Single Fiber Applying Magnetic Forces in Ambient Air - Szabadi, Julia; Meyer, Jörg; Dittler, Achim (Separations, 2023)
The potential utilization of magnetic effects in gas particle separation is a current subject of research. This paper demonstrates for the first time that a single magnetizable filter fiber can be deflected by a magnetically induced excitation for a selected combination of parameters, resulting in the removal of deposited particle structures with high detachment levels. A correlation between the magnetic flux density and achieved acceleration to overcome the adhesive forces/strength of the particle structure was determined. The degree of detachment after each regeneration was calculated by comparing the projection area before and after detachment using high-speed images. At a magnetic flux density of B = 38.5 mT, accelerations of maximum a = 105 m·s−2 are achieved, depending on the axial position along the single fiber. The degrees of regeneration achieved at these parameters depend on the amount of fiber loading and on the fiber orientation in the gravitational field. The horizontal orientation of the fiber leads to an increased reattachment of precedingly detached particle structures after deflection compared to a vertical orientation. High particle loading on the fiber results in enhanced detachment by inertia. Under the most favorable process conditions investigated, detachment levels of > 90% are achieved.